The perils of pay variability: Determinants of worker aversion to variable compensation in low- and middle-wage jobs - Lindsey D. Cameron; Jirs Meuris (PLoS ONE, 2026)
A substantial proportion of the labor force in low- and middle-wage jobs is prone to pay variability, or variance in earnings from paycheck to paycheck. Emerging research suggests that pay variability can be detrimental to workers’ well-being and enhance their likelihood of exiting their job. Using several iterations of qualitative and quantitative data, we identify and evidence critical determinants of workers’ experience of pay variability and their likelihood of voluntary turnover. Combining insights from exploratory interviews and surveys with ride-hailing drivers (N = 63) and cognitive appraisal theory, we predicted that pay variability is most likely to result in voluntary turnover when (a) workers were more frequently earning lower-than-average paychecks, (b) felt limited control over their earnings, and (c) their household was dependent upon their paycheck. Using matched survey and archival data from a sample of truck drivers (N = 711) from a national transportation company, we subsequently found that pay variability is positively associated with the likelihood of turnover, but this relationship significantly varied with the predicted contextual moderators. Additional quantitative analyses demonstrated that this relationship was observed even among the highest performing drivers and, surprisingly, likely resulted in less annual pay for those who left. Supplemental qualitative data provided further support for the predicted moderators. Taken together, our findings explain why and when variable compensation represents a source of precarity for low-and middle-wage workers that can motivate turnover. Theoretical and practical implications are discussed.